Early modern bromance love, friendship, and marriage in sixteenth-century Italian academies - Dal Molin, Aria (Cambria Press, 2020)
"This book resituates the contemporary genre of the bromance, as well as its surrounding cultural discourse, in the theatrical practices of early-sixteenth-century Italian academies, revealing how a group of early modern Italian academicians institutionalized alternative friendships between men to prolong male bonding. This study combines New Historicism with Queer Theory and scholarly discourse on film to analyze the early modern influences on the performative practices of masculinity and male friendships in the bromance of contemporary film, television, and media. This book therefore analyzes the lives and friendships of young Italian members of the early-sixteenth-century Accademia degli Intronati and their public theatrical performances that displayed homosocial triangles using women to strengthen the bonds between men, by referring to the work of Claude Lévi-Strauss, Gayle Rubin, and Eve Kosofsky Sedgwick. Taking a new approach to the homosocial triangle, this theory is further applied to theoretical discourses of perfect friendship (amicitia perfecta) as exemplified through the academy members testing its boundaries through narrative and performance. Ultimately, this book newly reveals how early modern Italian bromance narratives interrogate alternative roles of close male friendships, the love between men, and the confines of marriage, thus providing the foundation for the contemporary bromance. Early Modern Bromance: Love, Friendship, and Marriage in Sixteenth-Century Italian Academies is an important work for Italian Studies, Italian American Studies, Comparative Literature, Literature and Language Studies, Theater and Drama Studies, Gender and Sexuality Studies, and Film and Media Studies"--
Keywords: Geschichte 1400-1500; Drama; Eros -- Begriff, Motiv; Italienisch; Freundschaft -- Motiv; Ehe -- Motiv; Italian drama / Italy / Siena / History and criticism; Italian drama / To 1700 / History and criticism; Theater / Italy / Siena / History / 16th century; Siena (Italy) / Intellectual life / 16th century; Male friendship in literature; Male friendship in motion pictures; Triangles (Interpersonal relations) in literature; Triangles (Interpersonal relations) in motion pictures; Queer theory; Intellectual life; Italian drama; Theater; Italy / Siena; To 1700; Criticism, interpretation, etc; History